Meeting Breeding Potential in Organic and Low-Input Dairy Farming - Davis, Hannah; Stergiadis, Sokratis; Chatzidimitriou, Eleni; Sanderson, Roy; Leifert, Carlo; Butler, Gillian (Frontiers in Veterinary Science, 2020)
Low-input (LI) dairy farming, relying heavily on grazing, is increasing in popularity for perceived sustainability, welfare and milk nutritional quality benefits. However, there is little research into the breed suitability for these systems. The popular Holstein Friesians are not well suited to LI production as, to achieve their potential high yields, they require high levels of concentrate intakes and veterinary inputs. Holstein-Friesians were traditionally bred for high milk yields, which often correlate negatively with functional traits, such as fertility and health. This drives the need for alternative breed choices and UK dairy farmers use several crossbreeding practices. Additionally, classic measures of production efficiency (kg feed /litre of milk) are not the sole priority in LI systems, which also aim for improved health, fertility, forage conversion and milk quality. This study aimed to explore the effect of breeding strategy on LI and organic production in dairy systems, collecting data from 17 farms throughout England and Wales: 7 organic and 10 low-input-conventional systems with both purebred and crossbred cows from different breeds. Records from 1070 cows were collected, including background data, health, fertility, breeding and parity. Additionally, milk was analysed on four occasions (Autumn 2011 and Winter, Spring and Summer 2012). Principal components analysis was used to visualise the effect of management, Farm ID and stage of lactation on LI-production. The analysis clustered cows by Farm ID showing that individual management practice on each farm had the greatest impact on various production traits. Cows were allocated a composite score based on their yield, health records and milk fatty acid profile and a linear mixed effects model indicated (p<0.01) that cross-bred New Zealand Friesian cows scored highest whilst Dairy Shorthorn cows scored the lowest. This paper highlights weaknesses in current breeding programmes for LI and organic farms in UK, in terms of the alignment of breeds with husbandry practices. Additional research is needed to explore any gene by environment interactions to meet the true potential of individual cows and certain breeds under LI and organic management.